Guidelines for distributing local community products using the PPP (Public-Private Partnerships) - Sangpud, Worophong; Maitreesophon, Bampen; Janthadech, Nitidhorn; Lancaster, James; Vongsawat, Piriyaporn; Chaiyanan, Pakhuan (Journal of MCU Phetchaburi Review, 2026)
This article proposes a strategic approach to the distribution of local community products by emphasizing collaborative partnerships and network-based cooperation through the framework of Public-Private Partnerships (PPP). This model fosters inclusive participation among the public sector, private enterprises, and community stakeholders not as unilateral supporters, but as equal partners. Such collaboration enhances operational efficiency, promotes optimal use of resources, and contributes to sustainable economic outcomes. The partnership among the three key sectors is characterized by mutual reinforcement. Local entrepreneurs serve as producers and developers of products rooted in cultural capital; government agencies provide policy direction, financial support, and access to market channels; while the private sector plays a pivotal role in managing distribution systems and enhancing market competitiveness. The essence of PPP lies not merely in a division of roles but in the creation of mutual benefits that drive holistic development of community-based products. The author argues that the PPP approach represents a crucial mechanism for expanding the reach of local products in alignment with the dynamics of the modern economy. When effectively implemented, this model holds the potential to systematically strengthen grassroots economies and ensure sustainable development Keywords: Local community products, Distribution of products, Public-Private Partnerships